Organizing and Managing Ecoregional Programs: Analytical Description, Reviews, and Stakeholder Issues - Anandajayasekeram, A. (International Service for National Agricultural Research, 2003)
Ecoregional Programs (ERP) were initiated by the Consultative Group on International Agricultural Research (CGIAR) in the early 1990s to improve the management of natural resources in collaboration with national and regional partners. The programs focus on specific ecological and geopolitical regions and seek a balanced emphasis on production, natural resource management and social equity.